Tienhaarassa - Anonymous (Salt Lake City, UT : Project Gutenberg, 2006)
"Tienhaarassa" by Anonymous is a theatrical play written in the early 20th century. The narrative unfolds around the struggles of Aaro Koski, a former student who has succumbed to alcoholism, and his interactions with Vilho Tuulos, a determined pastor. The work likely explores themes of redemption, the impact of familial relationships, and the power of faith and hope against personal despair. The storyline primarily revolves around the poignant dialogue between Tuulos and Koski as they confront Koski's troubled past and present addiction. Tuulos attempts to guide Koski towards spiritual awakening and rescue him from his destructive lifestyle. Through a series of heartfelt conversations, Koski reflects on his familial relationships, recalling the influence of his parents and the memories of his deceased sister. The play delves into Koski's internal battles, highlighting his feelings of worthlessness and struggle against addiction, while Tuulos embodies compassion and perseverance, encouraging Koski to seek hope and change. Ultimately, the narrative hints at the possibility of redemption, portraying a powerful journey toward personal transformation. (This is an automatically generated summary.)
Release date is 2006-12-04
Produced by Matti Järvinen
Keywords: Drama